2007
DOI: 10.1111/j.1751-5823.2007.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

On Tests for a Normal Mean with Known Coefficient of Variation

Abstract: Hinkley (1977) derived two tests for testing the mean of a normal distribution with known coefficient of variation (c.v.) for right alternatives. They are the locally most powerful (LMP) and the conditional tests based on the ancillary statistic for μ. In this paper, the likelihood ratio (LR) and Wald tests are derived for the one- and two-sided alternatives, as well as the two-sided version of the LMP test. The performances of these tests are compared with those of the classical "t", sign and Wilcoxon signed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Their simulation results shown that, for the two-sided alternatives the likelihood ratio test or the Wald test is the best test. This paper extends the recent work of Bhat and Rao [1] to the confidence interval for the normal population mean with known coefficient of variation. We propose two new confidence intervals based on the estimator of the mean with known coefficient of variation of Searls [5] where he showed that the mean squares error of his proposed Suparat Niwitpong is with the Department of Applied Statistics, King Mongkut's University of Technology North Bangkok, Bangkok, THAILAND, 10800, e-mail: suparatn@kmutnb.ac.th estimator is lower than the unbiased estimator (the sample mean).…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Their simulation results shown that, for the two-sided alternatives the likelihood ratio test or the Wald test is the best test. This paper extends the recent work of Bhat and Rao [1] to the confidence interval for the normal population mean with known coefficient of variation. We propose two new confidence intervals based on the estimator of the mean with known coefficient of variation of Searls [5] where he showed that the mean squares error of his proposed Suparat Niwitpong is with the Department of Applied Statistics, King Mongkut's University of Technology North Bangkok, Bangkok, THAILAND, 10800, e-mail: suparatn@kmutnb.ac.th estimator is lower than the unbiased estimator (the sample mean).…”
Section: Introductionsupporting
confidence: 61%
“…However, in practice, there are situations in area of agricultural, biological, environmental and physical sciences that a coefficients of variation are known. For example, in environmental studies, Bhat and Rao [1] argued that there are some situations that show the standard deviation of a pollutant is directly related to the mean, that means the τ is known. Furthermore in clinical chemistry, " when the batches of some substance (chemicals) are to be analyzed, if sufficient batches of the substances are analyzed, their coefficients of variation will be known".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gleser and Healy [4] proposed the minimum quadratic risk scale-invariant estimator for the normal mean with known CV. Bhat and Rao [5] investigated the tests for a normal mean with known CV. Niwitpong et al [6] provided confidence intervals for the difference between normal population means with known CVs.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon arises in area of agricultural, biological, environmental, and physical sciences. For instance, in environmental science, Bhat and Rao [5] explain that there are some situations that show the standard deviation of a pollutant is directly related to the mean, which means is known. In clinical chemistry, Bhat and Rao [5] also state that "when the batches of some substance (chemicals) are to be analyzed, if sufficient batches of the substances are analyzed, their coefficients of variation will be known."…”
Section: Introductionmentioning
confidence: 99%